Dermal fibroma in olive barb Systomus sarana (Hamilton, 1822): a case study - Sahoo, M. K.; Rajesh Kumar, P.; Pattanayak, S.; Das, P. C.; Sahoo, P. K. (Indian Journal of Fisheries, 2017)
Systomus sarana (Hamilton, 1822) (weight; 370 g; length: 29.0 cm ) obtained from a carp polyculture pond revealed presence of a solid nodular tumorous mass on right dorso-lateral side of the body. Surgical excision and further histopathological examination of the focal non-invasive mass revealed that the tumor is a fibroma covered by thick stratified squamous epithelium. The fibroma had a compact fibrous stroma organised in whorls and bundles.